2007
DOI: 10.1016/j.cmet.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Orchestration of Cardiac Functions by the Orphan Nuclear Receptors ERRα and γ

Abstract: Orphan nuclear receptor ERRalpha (NR3B1) is recognized as a key regulator of mitochondrial biogenesis, but it is not known whether ERRalpha and other ERR isoforms play a broader role in cardiac energetics and function. We used genome-wide location analysis and expression profiling to appraise the role of ERRalpha and gamma (NR3B3) in the adult heart. Our data indicate that the two receptors, acting as nonobligatory heterodimers, target a common set of promoters involved in the uptake of energy substrates, prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
401
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 381 publications
(443 citation statements)
references
References 43 publications
32
401
3
Order By: Relevance
“…ChIP analysis was performed using the ChIP assay kit (Upstate Biotechnology) according to the manufacturer's instructions. For realtime PCR, we used primer pairs based on a previous report (15). 5Ј-GGAAACAGTTTCTGGCTAGGAATGCGTGA-3Ј and 5Ј-CTGCAAGGGGCAAAGGGTGAGAGGGAGGAGG-3Ј were used for the pyruvate dehydrogenase kinase 4 (PDK4) gene promoter region at ERR␣ response element, and 5Ј-ATG-AGGCGTAGTGCATAACCAA-3Ј and 5Ј-TTGATTGTAGA-GGCGAAAAGACC-3Ј were used for the PDK4 gene distal region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ChIP analysis was performed using the ChIP assay kit (Upstate Biotechnology) according to the manufacturer's instructions. For realtime PCR, we used primer pairs based on a previous report (15). 5Ј-GGAAACAGTTTCTGGCTAGGAATGCGTGA-3Ј and 5Ј-CTGCAAGGGGCAAAGGGTGAGAGGGAGGAGG-3Ј were used for the pyruvate dehydrogenase kinase 4 (PDK4) gene promoter region at ERR␣ response element, and 5Ј-ATG-AGGCGTAGTGCATAACCAA-3Ј and 5Ј-TTGATTGTAGA-GGCGAAAAGACC-3Ј were used for the PDK4 gene distal region.…”
Section: Methodsmentioning
confidence: 99%
“…However, by functional analysis in cultured cells and intact animals, ERR␣ appears functionally distinct from ER␣ and acts as a regulator in energy metabolism through control of fatty acid oxidation, mitochondrial biogenesis, and oxidative phosphorylation (14). Reflecting the physio-logic role of ERR␣, a number of ERR␣ target genes have been identified (15), and transcriptional function was shown to depend on chromatin environment of the promoters. Although no endogenous ligand has yet been found, synthetic ERR␣ ligands appear to modulate ERR␣ transcriptional activity as inverse antagonists (16,17).…”
mentioning
confidence: 99%
“…ERRγ is highly expressed in tissues with high metabolic activity (e.g. heart, kidney, slow-twitch muscle, BAT and CNS) and loss of this receptor in mouse results in neonatal death, presumably due to motor defects that prevent feeding Dufour et al 2007). …”
Section: Errsmentioning
confidence: 99%
“…Further studies indicated that ERRa can bind to and activate transcription through ERR-response elements (ERREs), which is different from those mediating the estrogenic response (Estrogen Response Elements, EREs). 9 ERRa can directly regulate tumor progression of various cancer cells via modulation of cell motility. Studies indicated that over expression of ERRa in xenografted breast cancer cells increases their metastatic capacities.…”
Section: Introductionmentioning
confidence: 99%